Creative arts therapies for the mental health of emerging adults: A systematic review. (February 2022) - Smriti, Diva; Ambulkar, Siddhant; Meng, Qiongyu; Kaimal, Girija; Ramotar, Kevin; Park, Sun Young; Huh-Yoo, Jina
Abstract: Emerging adults face significant risk of experiencing mental health problems, especially since most lifetime mental problems have first onset by age 24. Despite the pervasiveness of these issues, emerging adults face barriers in receiving help including stigma surrounding help-seeking behavior and negative attitudes about perceived usefulness of therapy. Creative and expressive art therapies (CATs) can address these needs by providing potentially destigmatized, non-invasive approaches to mental health care. To examine how this population can benefit from CAT, we conducted a systematic review of the literature to understand the types of CAT interventions that have been empirically tested among emerging adults. From a total of 7276 articles published between 1985 and 2020, we filtered down to 11 studies, both qualitative and quantitative, meeting our inclusion and exclusion criteria. Results showed art therapy and poetry therapy were the most frequently studied CATs for the emerging adult population; and art therapy studies comprised the largest proportion of studies reporting statistical significance on its efficacy among all CATs reviewed. We highlight the need for more studies using replicable, generalizable methods in evaluating CAT. We then discuss implications for counselors, practitioners, and clinician-researchers interested in using CAT to improve mental health care among emerging adults. Highlights: Emerging adults face significant risk of suffering from mental health disorders. Creative and expressive art therapies (CATs) help by providing destigmatized approach. Art therapy and poetry therapy were the most frequently studied CATs. Fewer studies on drama therapy and music therapy were found, with no studies on dance movement therapy. Majority of art therapy studies reported statistical significance on its efficacy.